Synthesis and Crystal Structure of a New La(III) Coordination Polymer Assembled from 2,4’-Diphenic Acid and Auxiliary Ligands - Wang, Aidong; Li, Wenbo; Guo, Feng; Zhang, Xiuling (Asian Journal of Chemistry, 2010)
A new metal coordination polymer [La 2(dpa)3(2,2'-bipy)2(H2O)]H2On (H2dpa = 2,4'-biphenyldicarboxylic acid and 2,2'-bipy = 2,2'-bipyridine) has been synthesized and structurally characterized by elemental analysis and X-ray diffraction. The crystal is triclinic, P-1 group with a = 9.594(5) Å, b = 13.472(5) Å, c = 22.475(5) Å, a = 104.079°, b = 90.007°, g = 101.209°, Mr = 1394.87, V = 2760.5(19) Å3, Dc = 1.678 g/cm3, F(000) = 1388 and Z = 2. In the present compound, the two La(III) ions are in different coordination environments. Two La(III) are linked together through dpa ligand, give rise to a binuclear La(III) cluster and form a 2-D (4,4) net.